Differential heart rate responses to social and monetary reinforcement in women with obesity. (12th February 2016) - Kube, Jana; Schrimpf, Anne; García‐García, Isabel; Villringer, Arno; Neumann, Jane; Horstmann, Annette
Abstract: Obesity is often accompanied by weight stigmatization; subsequently, individuals with obesity frequently face social rejection. It has been shown that recurrent negative social experiences can alter the perception of social cues. However, the way individuals with obesity process social stimuli is not well understood. This study aims to investigate obesity‐related alterations in social compared to nonsocial information processing. Women with obesity ( n = 14) and without obesity ( n = 14) participated in a social and a monetary incentive delay task in which they anticipated and received positive, negative, and neutral outcomes in the form of faces or money. During the experiment, phasic heart rate changes and reaction times were measured. Women with obesity, compared to lean women, exhibited a stronger differentiation during the anticipation of monetary and social reinforcement, showing slower reaction times to social cues compared to monetary cues. During the outcome processing phase, women with obesity relative to controls demonstrated diminished heart rate responses particularly to negative social outcomes. Interestingly, differences in cardiac responses in participants with obesity were moderated by weight‐related teasing experiences. In women with obesity, a higher BMI was associated with blunted cardiac responses to social cues relative to monetary cues only if they reported more emotional pain after weight‐related teasing. Our results contribute to a better understanding of social information processing in obesity and give first evidence for the role of negative social experiences in reinforcement processing.